2022
DOI: 10.1039/d2fo02131e
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of fermented yak milk-derived peptide LYLKPR on H2O2-injured HT-22 cells

Abstract: This study explored the neuroprotective effect of the peptide LYLKPR derived from fermented yak milk by Lactiplantibacillus plantarum JLAU103 on H2O2-injured HT-22 cells. Peptide LYLKPR showed good stability in the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Western blotting analysis demonstrated that AR-10 and CP-8 increased the expression level of Nrf2 in H 2 O 2 -induced HepG2 cells while decreasing the expression level of Keap1 (Figure D,E). Multiple studies have also supported the notion that antioxidant peptides could regulate the Keap1/Nrf2 pathway by increasing the expression of Nrf2 and inhibiting Keap1, thereby preventing the occurrence of oxidative stress-related diseases. , …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Western blotting analysis demonstrated that AR-10 and CP-8 increased the expression level of Nrf2 in H 2 O 2 -induced HepG2 cells while decreasing the expression level of Keap1 (Figure D,E). Multiple studies have also supported the notion that antioxidant peptides could regulate the Keap1/Nrf2 pathway by increasing the expression of Nrf2 and inhibiting Keap1, thereby preventing the occurrence of oxidative stress-related diseases. , …”
Section: Discussionmentioning
confidence: 97%
“…Multiple studies have also supported the notion that antioxidant peptides could regulate the Keap1/Nrf2 pathway by increasing the expression of Nrf2 and inhibiting Keap1, thereby preventing the occurrence of oxidative stress-related diseases. 50,51 To further evaluate the interaction between AR-10 and CP-8 with Keap1-Nrf2, a molecular docking analysis of these peptides with Keap1 was conducted. The results revealed that AR-10 could form hydrogen bonds or salt bridges with the key amino acids Tyr334, Arg380, Asn414, Arg415, and Ser602 in the Kelch domain cavity.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Fermenting milk protein with lactic acid bacteria is a low-cost and convenient method for obtaining a large number of bioactive peptides. Bifidobacterium longum , peptide PIGSEN­ SEKTTM­PLW released by casein fermentation by Lactobacillus helveticus , and LYLKPR obtained by yak milk fermentation by Lactobacillus plantarum have been shown to pass through the BBB model in vitro, having ACE inhibition and neuroprotective activities, respectively. , However, the role of these peptides in vivo also depends on their stability in blood, half-life, and affinity with receptors. At present, milk-derived opioid peptides mainly bind to receptors, but it is unclear whether they bind to δ and κ receptors.…”
Section: Peptides That Can Penetrate the Bbbmentioning
confidence: 99%